1994
DOI: 10.1089/thy.1994.4.93
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model of Thyroid Hormone-Induced Bone Loss: Effect of Antiresorptive Agents on Regional Bone Density and Osteocalcin Gene Expression

Abstract: Thyroid hormone has been shown to stimulate bone resorption. Both endogenous hyperthyroidism and exogenous thyroxine suppressive therapy have been associated with reduction in bone mineral density (BMD), but the patholophysiology of thyroxine-induced bone loss is not well understood. First we studied the effect of L-T4 (0.1-0.3 microgram/g body weight ip/day) on bone turnover in rats by measuring regional BMDs and osteocalcin mRNA. Next we determined whether antiresorptive agents (calcitonin 1 microU/gip/day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
14

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
1
8
0
14
Order By: Relevance
“…Hypothyroid patients have reduced levels of serum OC, which are rapidly normalized after T 4 treatment. Rats treated with excessive levels of thyroid hormone have a dose-dependent increase in the levels of OC mRNA in the femur (Ross & Graichen 1991, Kung & Ng 1994. In situ hybridization experiments document that T 4 treatment increases expression of OC mRNA in femoral osteoblasts, but not in vertebral osteoblasts (Kung & Ng 1994), pointing towards a differential response of vertebral and femoral osteoblasts to thyroid hormone.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hypothyroid patients have reduced levels of serum OC, which are rapidly normalized after T 4 treatment. Rats treated with excessive levels of thyroid hormone have a dose-dependent increase in the levels of OC mRNA in the femur (Ross & Graichen 1991, Kung & Ng 1994. In situ hybridization experiments document that T 4 treatment increases expression of OC mRNA in femoral osteoblasts, but not in vertebral osteoblasts (Kung & Ng 1994), pointing towards a differential response of vertebral and femoral osteoblasts to thyroid hormone.…”
Section: Introductionmentioning
confidence: 94%
“…Rats treated with excessive levels of thyroid hormone have a dose-dependent increase in the levels of OC mRNA in the femur (Ross & Graichen 1991, Kung & Ng 1994. In situ hybridization experiments document that T 4 treatment increases expression of OC mRNA in femoral osteoblasts, but not in vertebral osteoblasts (Kung & Ng 1994), pointing towards a differential response of vertebral and femoral osteoblasts to thyroid hormone. Rats treated with high dose T 4 for 28 days have reduced bone mineral density in the femur but not in the spine, corresponding to the regions of thyroid hormoneinduced OC mRNA expression (Gouveia et al 1997).…”
Section: Introductionmentioning
confidence: 94%
“…Mice with random blood glucose level >17 mmol/L (normal: random 7.1-8.2 mmol/L) were considered diabetic. The mice of the DH and H groups were intraperitoneally injected with LT4 (0.3 mg/kg body weight) (Kung and Ng, 1994;Chandra et al, 2010;Kim et al, 2012) on a daily basis till the end of the experiment. The experimental mice were kept without any type of reversal treatment such as insulin or methimazole, throughout the study period.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Studies in the rat have supported this hypothesis (Eriksen et al, 1985;Yamamoto et al, 1993b). Biochemical markers of bone turnover have also been shown to be increased in the rat (Harvey et al, 1991;Kung and Ng, 1994;Taimela et al, 1994;Ishihara et al, 1997). Taken together, these results suggest that patients with hyperthyroidism could potentially benefit from therapy that prevents the increased bone turnover and bone loss.…”
mentioning
confidence: 75%
“…Previous reports (Ongphiphadhanakul et al, 1993;Kung and Ng, 1994;Ishihara et al, 1997) have shown that excess thyroid hormone in rats causes increased levels of the bone formation markers, osteocalcin and alkaline phosphatase, and the resorption markers, tartrate-resistant acid phospha- tase, pyridinoline, and Dpd. Ongphiphadhanakul et al (1993) have shown that after 3 weeks of treatment in male hyperthyroid rats with a bisphosphonate, femoral mRNA levels of tartrate-resistant acid phosphatase and alkaline phosphatase were reduced compared with T4 controls.…”
Section: Discussionmentioning
confidence: 95%